Global innovation races, offshoring and wage inequality - Impullitti, Giammario (Wiley, 2016)
In the 1970s and 1980s the US position as the global technological leader was increasingly challenged by Japan and Europe. In those years the US skill premium and residual wage inequality increased substantially. This paper presents a two-region, quality-ladder growth model where the lagging economy progressively catches up with the leader. As the innovation gap closes, the advanced country experiences fiercer foreign technological competition that forces its firms to innovate more. Faster technical change increases the skill premium and residual inequality. Offshoring production and innovation plays a key role in shaping the link between international competition and inequality.